Participatory Modeling Updates Expectations forIndividuals and Groups, Catalyzing BehaviorChange and Collective Action inWater‐Energy‐Food NexusGovernance. Issue 12 (17th December 2019) - Kimmich, C.; Gallagher, L.; Kopainsky, B.; Dubois, M.; Sovann, C.; Buth, C.; Bréthaut, C.
Abstract: Participatory modeling is a potentially high‐impact approach for catalyzing fundamental sustainability transformations. We test if participation in a group system dynamics modeling exercise increases participants' agency through a novel method to evaluate potential behavioral change using expectation measures. A water‐energy‐food nexus—a functionally interdependent but underconceptualized system with low consensus and high scientific uncertainty—was mapped, and its evolution simulated by 46 participants in three interventions in a region undergoing hydropower infrastructure development in Northeastern Cambodia. Participants' system‐related expectations were measured before and after the interventions. Our results suggest that participants became significantly more optimistic about their individual agency to increase agricultural and fishing income and, interestingly, less likely to participate in local government development planning procedures. Findings also reveal how some uncertainties for multiple variables were reduced within and across the groups. Such converging expectations suggest that participatory modeling could contribute to making collective solutions and institutionalized agreements more likely. This research contributes to innovation in sustainability because it unpacks some underlying mechanics of how participatory processes can lead to new adaptive capacities, shared perspectives, and collective actions. Plain Language Summary: Our research contributes to understanding actionable knowledge for sustainability using a before‐after intervention with fishing and farming community representatives in a situation of conflicting water, energy, food, and livelihoods priorities in rural Cambodia. We explain why reducing uncertainty and building consensus on action through participatory research could potentially catalyze new behavior that promotes sustainability and test how this happens in our intervention. The result is a new and much needed evaluation framework and method for behavioral change outcomes in sustainability interventions. Key Points: Participatory modeling could be fundamental to understanding complex social‐ecological systems with high uncertainty and conflicting interests Engagement in participatory modeling can change expectations and thereby increase individual and collective agency in facing sustainability challenges Our method provides a framework to evaluate and compare participatory modeling approaches for their behavior change potential